Symposia on Collaboration in Aircraft Design (SCAD) - Dieter Scholz (2024)
Information exchange, collaboration, cross-validation, harmonization of research in aircraft design.
Keywords: aerospace; aeronautics; air transportation; aeroplane; aircraft; design; research; symposium; Europe; university; industry; exchange; collaboration; harmonization; community; CEAS; TCAD; SCAD; publishing; Open Access; journal; proceedings